Laboratory examinations for the vestibular system. Issue 1 (February 2018) - van de Berg, Raymond; Rosengren, Sally; Kingma, Herman
Abstract : Purpose of review: In the last decades, researchers suggested that clinical assessment of labyrinthine function in detail became easy thanks to video head impulse tests (VHITs), vestibular evoked myogenic potential test (VEMP) and video-oculography (VOG). It has been argued that they can replace electronystagmography, the caloric and rotatory chair tests. This review addresses the latest evaluations of these tests and the opportunities they offer, but also the limitations in clinical practice. Recent findings: The VHIT and suppression head impulse test (SHIMP) are under ideal circumstances able to accurately identify deficits of the VOR in 3D. However, in a relevant part of the patient population, pupil tracking is inaccurate, video-goggles slip and VOR quantification is problematic. The dissociation between the VHIT and caloric test suggests that these tests are complementary. A new 3D-VOG technique claims to quantify eye torsion better than before, opening multiple diagnostic possibilities. VEMPs remain difficult to standardize. Variability in normal cervical vestibular-evoked myogenic potential amplitude is large. VEMPs become smaller or absent with age, raising questions of whether there is a lower normal limit at all. Recent research shows that the labyrinth is directly stimulated in the MRI offering new opportunities for diagnostics and research. Summary: In clinical practice, the VHIT, SHIMP, VEMP and new 3D-VOG techniques improve diagnostic power. Unfortunately, technical issues or variability prevent reliable quantitative evaluation in a part of the regular patient population. The traditional caloric and rotatory chair test can still be considered as valuable complementary tests.